2023
DOI: 10.5530/bems.9.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ChatGPT Tool to Assess the Potential of its Utility for Academic Writing in Biomedical Domain

Abstract: Background: ChatGPT (Generative Pre-trained Transformer) is an artificial intelligence chatbot which is designed to generate detailed text response and/or articulate answers to any query. Widespread concerns are expressed that such tools can be misused for academic writing. Hence this study was designed to test the utility and merit of ChatGPT for academic writing in biomedical sciences. Materials and Methods: five randomly selected quey topics were input into ChatGPT for a response. The ChatGPT response time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Interestingly, a recent preprint by Benoit showed the promising potential of ChatGPT in rapidly crafting consistent realistic clinical vignettes of variable complexities that can be a valuable educational source with lower costs [ 67 ]. Thus, ChatGPT can be useful in health care education including enhanced communication skills given proper academic mentoring [ 42 , 57 , 67 ]. However, the copyright issues should be taken into account regarding the ChatGPT-generated clinical vignettes, aside from the issue of inaccurate references [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent preprint by Benoit showed the promising potential of ChatGPT in rapidly crafting consistent realistic clinical vignettes of variable complexities that can be a valuable educational source with lower costs [ 67 ]. Thus, ChatGPT can be useful in health care education including enhanced communication skills given proper academic mentoring [ 42 , 57 , 67 ]. However, the copyright issues should be taken into account regarding the ChatGPT-generated clinical vignettes, aside from the issue of inaccurate references [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent preprint by Benoit showed the promising potential of ChatGPT in rapidly crafting consistent realistic clinical vignettes of variable complexities which can be a valuable educational source with lower costs [45]. Thus, ChatGPT can be useful in healthcare education including enhanced communication skills given proper academic mentoring [22,45,67]. However, the copyright issue in ChatGPT-generated clinical vignettes besides the issue of inaccurate references should be taken into account [45].…”
Section: Discussionmentioning
confidence: 99%
“…Though promulgated with varying degrees of hesitancy, speculative use-cases have spanned hospital discharge summaries, 16 medical information and patient medical record accessibility, 17,18 trainee education and evaluation, 19,20 and academic writing. 7,8,21,22 While a preponderance of commentaries/editorials on the topic have emerged since 2022, scientifically rigorous appraisal of LLMgenerated academic literature remains limited. 23 To our knowledge, only one such analysis has been conducted using ChatGPT, wherein Gao et al presented AI-generated and human-written abstracts to a group of blinded reviewers, and found that human reviewers were mostly successful in identifying on a binary scale abstract that had been written by AI, often noting them to be more vague.…”
Section: Discussionmentioning
confidence: 99%